2000
DOI: 10.1046/j.1365-3059.2000.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of the pathogen Phytophthora parasitica by arbuscular mycorrhizal fungi is a consequence of effects on infection loci

Abstract: The impact of colonization by the arbuscular mycorrhizal fungus (AMF) Glomus mosseae on tomato root necrosis caused by the soil-borne pathogen Phytophthora parasitica was investigated. Studies in situ permitted infection loci to be identified and the effects of the AMF on numbers to be elucidated. Effects were significant and, 7 and 16 days after inoculation with zoospores of the pathogen, roots of plants colonized by the AMF had 39% and 30%, respectively, fewer infection loci than those that were not. Concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 21 publications
3
68
0
2
Order By: Relevance
“…As mudas micropropagadas no sistema atual podem ir a campo com diversos porcentuais de colonização micorrízica, eventualmente até sem a presença do fungo. O estabelecimento do FMA antes do ataque do patógeno pode induzir aumento da resistência da planta (Mark & Cassels, 1996;Vigo et al, 2000).…”
Section: Introductionunclassified
“…As mudas micropropagadas no sistema atual podem ir a campo com diversos porcentuais de colonização micorrízica, eventualmente até sem a presença do fungo. O estabelecimento do FMA antes do ataque do patógeno pode induzir aumento da resistência da planta (Mark & Cassels, 1996;Vigo et al, 2000).…”
Section: Introductionunclassified
“…Indeed, co-culture of the non-mycorrhizal species Dianthus caryophyllus with the mycorrhizal species Tagetes patula in presence of G. intraradices clearly reduced the disease caused by F. o. dianthi in D. caryophyllus in a manner clearly unrelated to plant nutrition which suggests a reduction in the pathogen development within the mycorrhizosphere (St-Arnaud et al, 1997). Moreover, a reduction in the number of infection loci of tomato roots pre-colonized with G. mosseae and inoculated with P. nicotianae zoospores infers that the pathogen may be affected prior to root penetration in the mycorrhizosphere (Vigo et al, 2000).…”
Section: The Mycorrhizosphere: a Zone Unfavorable To Pathogen Developmentioning
confidence: 94%
“…It has been found that the chemical treatments are not efficient in controlling these diseases and pests. AMF has been demonstrated to have high biocontrol potential of plants against many pests (Quarles, 1999), especially for plant diseases caused by Phytophtora and Fusarium pathogens (Vigo et al, 2000). These observations suggest that AMF may affect plant and soil microbial activities by stimulating the production of root exudates, phytoalexins, and phenolic compounds (Morandi, 1996;Jaiti et al, 2007).…”
Section: Mycorrhizal Fungi As Bioprotectants In Date Palmsmentioning
confidence: 99%